Cost-Effectiveness and Quality of Care of a Comprehensive ART Program in Malawi. Issue 21 (May 2016) - Orlando, Stefano; Diamond, Samantha; Palombi, Leonardo; Sundaram, Maaya; Shear Zimmer, Lauren; Marazzi, Maria Cristina; Mancinelli, Sandro; Liotta, Giuseppe
Abstract : Abstract: The aim of this study is to assess the cost-effectiveness of a holistic, comprehensive human immunodeficiency virus (HIV) treatment Program in Malawi. Comprehensive cost data for the year 2010 have been collected at 30 facilities from the public network of health centers providing antiretroviral treatment (ART) throughout the country; two of these facilities were operated by the Disease Relief through Excellent and Advanced Means (DREAM) program. The outcomes analysis was carried out over five years comparing two cohorts of patients on treatment: 1) 2387 patients who started ART in the two DREAM centers during 2008, 2) patients who started ART in Malawi in the same year under the Ministry of Health program. Assuming the 2010 cost as constant over the five years the cost-effective analysis was undertaken from a health sector and national perspective; a sensitivity analysis included two hypothesis of ART impact on patients' income. The total cost per patient per year (PPPY) was 314.5 for the DREAM protocol and 188.8 for the other Malawi ART sites, with 737 disability adjusted life years (DALY) saved among the DREAM program patients compared with the others. The Incremental Cost-Effectiveness Ratio was 1640 per DALY saved; it ranged between 896–1268 for national and health sector perspective respectively. The cost per DALY saved remained under 2154 that is the AFR-E-WHO regional gross domestic product per capita threshold for a program to be considered very cost-effective. HIV/acquired immune deficiency syndrome comprehensive treatment program that joins ART with laboratory monitoring, treatment adherence reinforcing and Malnutrition control can be very cost-effective in the sub-Saharan African setting.